1986
DOI: 10.1177/073168448600500301
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Induced Transverse Cracking in Graphite-Epoxy Cross-Ply Laminates

Abstract: Thermally induced transverse cracking in T300/5208 graphite-epoxy cross-ply laminates was investigated experimentally and theoretically. The six laminate configura tions studied were: [0/903] s, [02/902]s, [03/90] s, [90/03]s, [902/02] s, and [903/0]s. The thermal load required to initiate transverse cracking was determined experimentally and compared to theoretical prediction. Experimental results for the accumulation of transverse cracks, under cyclic thermal loading between —250°F and 250°F for up to 500 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 5 publications
2
37
0
Order By: Relevance
“…Figure 5 shows that the main damage in the material was the splitting of fiber bundles and that the microcracks developed in the direction of fiber orientation. This is similar to traditional laminates of which transverse cracks are the main damage induced by thermal cycles [9] . The microcracks were reported to span the entire cross section.…”
Section: X-ray Ct Observationmentioning
confidence: 82%
See 1 more Smart Citation
“…Figure 5 shows that the main damage in the material was the splitting of fiber bundles and that the microcracks developed in the direction of fiber orientation. This is similar to traditional laminates of which transverse cracks are the main damage induced by thermal cycles [9] . The microcracks were reported to span the entire cross section.…”
Section: X-ray Ct Observationmentioning
confidence: 82%
“…It was found that the damage was more extensive in 934 epoxy resin composites and included skin/core delamination. Adam et al [9] emulated the effect of a space environment for T700/5208 carbon epoxy resin specimens with various symmetrical lay-ups. He noted that no crack saturation was observed even after 500 cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber splitting has also been reported in some materials [17]. Crack densities are generally observed to increase with the number of cycles until a saturation value is achieved [17,[22][23].…”
Section: ]mentioning
confidence: 99%
“…Unconstrained thermal cycling has been shown to induce microcracking in the transverse plies of polymer matrix composites [7,[15][16][17][18][19][20][21][22][23][24]. Fiber splitting has also been reported in some materials [17].…”
Section: ]mentioning
confidence: 99%
See 1 more Smart Citation